Polymer supported oxazolidin-2-ones derived from L-serine - a cautionary tale - Bew, S; Bull, S; Davies, S (2000)
The capacity of N-Boc-4-hydroxymethyl-oxazolidin-2-ones to undergo rapid O-O and N-O acyl transfer makes these serine derived chiral auxiliaries unsuitable for attachment to polymers. (C) 2000 Elsevier Science Ltd.